Analisis Kepemimpinan, Kecerdasan Emosional, dan Kualitas Pelatihan dalam Meningkatkan Efektivitas Pengambilan Keputusan dan Kinerja Personel Kepolisian - Rahmatia Pakaya; Nur Fadli Umar; Nurifana Umar (Asosiasi Peneliti dan Pengajar Ilmu Hukum Indonesia, 2026)
The effectiveness of public organizations is strongly influenced by leadership quality and employee productivity. Effective leadership plays a crucial role in directing, supervising, and motivating members to achieve organizational goals optimally. This study aims to analyze public sector leadership practices at the Limboto Sector Police Office (Polsek Limboto) by focusing on four key aspects: decision-making, communication, supervision, and motivation. A descriptive qualitative approach was employed to gain an in-depth understanding of leadership implementation within the police organization. Research data were collected through observation, interviews, and documentation and analyzed using the data analysis model developed by Miles, Huberman, and Saldana. The findings indicate that the Head of Polsek Limboto applies an effective democratic leadership style that encourages member participation in organizational processes. Decision-making is conducted by considering input from personnel, while two-way communication enables the accommodation of aspirations and fosters harmonious working relationships. Furthermore, supervision is carried out in a disciplined yet persuasive manner and is supported by the consistent implementation of a reward and punishment system. This leadership approach has been proven to positively influence both the quality and quantity of personnel performance, thereby supporting the effective and sustainable achievement of organizational goals within the police institution.